ADOPSI INOVASI USAHA ISTRI NELAYAN DI BLIMBINGSARI BANYUWANGI - Fatmah Fatmah (Jurnal Akuntansi dan Pajak, 2024)
This article aims to examine what factors cause the unsuccessful adoption of business innovations among fisherwives in Blimbingsari Village. The findings of this study are expected to assist the government in identifying concrete measures to help improve the welfare of fishermen. That way the government's programme to spur the development of the marine and fisheries sector can be realised from upstream to downstream which not only focuses on increasing fish production but also innovating to provide added value. The population in this study were fishermen's wives in Blimbingsari Village, Banyuwangi Regency. The sampling technique used was simple random sampling. A total of 214 respondents were obtained as research samples. The data analysis used in this study was path analysis. The results showed that this research model was able to explain the theory clearly. Variables of innovation characteristics, adopter characteristics, social systems, and communication channels have a positive direction towards innovation adoption.